Design and implementation of circuit optimization in VLSI: A review - K. Kalpana; S. Ramya; A. Purushothaman (AG Volumes, 2023)
Digital circuits streamline transistor functioning and enable switch-based device construction. There were significant drawbacks to the introduction of the vacuum tube into the electronics sector, such as the need for high power and a hundred anode tension. The development of the transistor required very little power in the field of microelectronics. It paved the way for future energy-efficient home appliances. Reduced functionality and more power per unit space have resulted from the integration of several functions onto a single chip and improved circuit performance, and these trends have been accompanied by an increase in the need for heat removal & cooling systems. Their primary problem in the VLSI setting is a lack of power. Today, optimization should focus on power, environment, and efficiency. The past was marked by extremely significant efficiency, expenditure, and production with a little weakening in power. The requirement for low power utilization and the high-speed processing has risen as a result of the incredible battery power development, a complicated practical technology like a computer system, electronic gadgets, mobile cellphones, implanted equipment, and digital portable devices. The high temperature activity of the powerful machine exacerbates the other defects in the silicone.